Réponses

Meilleure réponse !
2014-05-14T15:15:58+02:00
 \frac{5}{4}- \frac{7}{2} +  \frac{3}{4}=  \frac{5}{4}- \frac{14}{4} +  \frac{3}{4} =  \frac{-9}{4} +  \frac{3}{4}=  \frac{-6}{4} =  -\frac{3}{2}

voila bonne journée.
Tu vois cette fois
nn mais c est bon c est plus la peine j ai réussi à le faire merci bcp quand même :)
[tex] \frac{5}{4}- \frac{7}{2} + \frac{3}{4}= \frac{5}{4}- \frac{14}{4} + \frac{3}{4} = \frac{-9}{4} + \frac{3}{4}= \frac{-6}{4} = -\frac{3}{2}[/tex]
Merci:)
De rien
2014-05-14T15:18:54+02:00